BIOSORPTION VANADIUM RECOVERY FROM FOSSIL FUEL POWER PLANT WASTEWATER - K. Imandel; M. Ghotbi-Ravandi; N. Moazami; M. Mazaheri Asadi (Tehran University of Medical Sciences, 1999)
Fossil fuel power plant is one of the most important sources of environmental pollution of the vanadium toxic metal. This survey showed that the Penicilium austuranium is the best microorganism for biosorption of vanadium isolated from environment of fossil fuel power plant. To determine the optimum pH and most biosorption and accumulation of vanadium by these fungi, power plants wastewater, passed through a cylindrical laboratory vessel, containing a great mass of this microorganism. When the concentration of 1000 ppm vanadium solution with 120 m1/h speeds, was passed through the above mentioned container, after 10 min, the laboratory experiment showed that the absorption was 100% and by the concentration, the time, was reduced. The best biosorption occurred with pH lower than 2, because vanadium acted as a cationic element, but in pH more than 2, vanadium was adsorbed to the cell fungi as anionic element and the sorption reduced. The alkaline condition stopped the vanadium sorption on the outer surface of the fungi. For isolation and recovery of vanadium, one can use water from distributed water supply networks.